Draft Genome Sequence of Rhodosporidium toruloides CECT1137, an Oleaginous Yeast of Biotechnological Interest - Morin, Nicolas (American Society for Microbiology, 2014)
We report the sequencing of the basidiomycetous yeast Rhodosporidium toruloides CECT1137. The current assembly comprises 62 scaffolds, for a total size of ca. 20.45 Mbp and a G+C content of ca. 61.9%. The genome annotation predicts 8,206 putative protein-coding genes.